Evaluasi Kompleksitas dan Aksesibilitas Produk Untuk Kemudahan Proses Pembongkaran - Nursanti, Ida; Rahmawati, Desi; Djunaidi, Much; Anis, Muchlison (Program Studi Teknik Industri, Universitas Muhammadiyah Surakarta, 2018)
Water pump machines are electronic products that are widely used by the community. Because of the high frequency of use, this product is quickly damaged. In order to reduce the environmental impact, the ease of the product to be repaired or recycled needs to be improved, especially the dismantling process because it is the initial process to separate components. This study aims to evaluate the ease of dismantling a water pump machine based on the ease of component to be reached and the complexity of the component and product design. Evaluation begins by identifying the initial product design and the relationships between components needed to determine the order of possible product demolition and as an attribute of calculating complexity and accessibility indexes. The calculation results show that the complexity and accessibility idex values for each component are the same in all disassembly sequences because the product design does not allow for sub-assembly. The most complex components are mechanical seal, water reservoirs and lids beside the pump body. While the components that are most difficult to access are impellers, mechanical seals and rator covers.